The greatest possible blessing: Calvin and deification - Mosser, Carl (Scottish journal of theology, 2002)
Many assume that the patristic notion of deification is absent from the mainstreams of post-patristic Western theology. Recent scholarship, however, identifies deification in Augustine, Aquinas, Luther, early Anglicanism, early Methodism and Jonathan Edwards – all fountainheads of Western theology. This article contends that deification is also present in Calvin's theology. It is not a prominent theme in its own right and some of the bolder patristic terminology is not employed. Nonetheless, the concept and imagery of deification regularly appear on stage while other doctrines are explicated. For Calvin, deification is the eschatological goal and blessing greater than which nothing can be imagined.